PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASISSTED INDIVIDUALIZATION (TAI) UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATERI ALAT OPTIK KELAS XI MIA 5 SMAN 1 PEKANBARU - Yuhandi, Rezky Ahmed; Irianti, Mitri; Fakhruddin Z, Fakhruddin Z (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the increase in learning motivation of students of class XI MIA 5 in SMAN 1 Pekanbaru in Optical Instrument material through the implementation of cooperative learning model, in Team Assisted Individualization type. This type of study is a pre-experimental One Group Pretest-Posttest Design. The subject of this study were students of class XI MIA 5 in SMAN 1 Pekanbaru, with 35 students. Data collection is done by giving the initial motivation questionnaire and final motivation questionnaire to students. Data analysis was carried out descriptively. The result showed that the average score of final motivation was obtained an increase from the average score of initial motivation with score difference 0.45. Based on data analysis, it can be concluded that the cooperative learning model of the Team Assisted Individualization type can improve student learning motivation.Key Words: Cooperative Learning Model Team Assisted Individualization Type, StudentMotivation, Optical Instruments.